Clinical and Radiodensitometric Evaluation of Ozonated Olive Oil in the Management of Periodontal Condition in Smoker Patients (Indian Journal of Public Health Research & Development, 2020)
Background and Objective: This study was designed to evaluate clinically and radiographically the role ofOzonated olive oil in the management of periodontal status in smoking patients.Materials and Method: The study was performed on twenty four medically free patients having chronicperiodontitis. Radiographic bone density evaluation as well as linear alveolar bone level and clinicalperiodontal parameters were recorded after the initial phase of plaque control then, the patients wereinstructed to perform oral hygiene measures. The clinical parameters which were included are; plaque index,gingival index, probing depth and clinical attachment loss. The patients were divided into 2 main groups,the first group received Ozonated olive oil while the second group served as control group. At baseline,three and six months, bone density and alveolar bone level were radiographically recorded using CBCT.The statistical analysis of the collected clinical and radiographic data revealed an overall clinical as wellas Radiometric and Densitometric measurements improvement by time for the Ozonated olive oil group incomparison to the control group at baseline, three and six months.Results: Ozonated olive oil group showed significant difference regarding the control group.Conclusion: The results of the current study revealed that the use of Ozonated olive oil can enhance bonelevel and density as well as tissue healing in periodontially affected teeth. In addition, the use of CBCT isconsidered as an effective method for evaluation of preoperative and postoperative alveolar bone.
Keywords: Ozonated olive oil, Periodontal condition, Smoker Patients